PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP PENGEMBANGAN KARIR PADA KARYAWAN PENDUKUNG AKADEMIK PERGURUAN TINGGI SWASTA X - Herlin Herlin (Universitas Mercu Buana, 2018)
This study aims to explain the influence of organizational culture and organizationalcommitment to career development. This study uses descriptive analysis research model andmultiple linear analysis. Data is collected by distributing questionnaires to 113 employeesworking in Private Higher Education X and research is based on cases that are happening inPrivate Higher Education X. The results of multiple linear regression analysis showed thatsimultaneously and partially the Organizational Culture variable had no effect on the CareerMining. However, Organizational Commitment has an influence on Career DevelopmentEmployee Supporting Academic. (1) there is no partial influence between the OrganizationalCulture on Career Development (2) partially there is a positive and significant influencebetween organizational commitment to career development.